Law Enforcement of Environmental Destruction Crimes in the PT TPL Agrarian Dispute in North Sumatra - Kasim, Nurhalisa (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This study examines law enforcement against environmental destruction in agrarian disputes PT Toba Pulp Lestari (PT TPL) in North Sumatra through a juridical-empirical approach that combines normative legal analysis with empirical findings from legal documents, field reports, and scientific data. The results indicate that the environmental damage meets the elements of an environmental crime and can be classified as a corporate offense, particularly due to discrepancies between the company’s operational activities, licensing requirements, and the precautionary principle. Scientific evidence plays a crucial role in establishing a causal relationship between the company’s activities and ecological degradation. However, law enforcement still faces structural obstacles, including weak inter-agency coordination and the dominance of administrative measures over criminal instruments. This study emphasizes the need to strengthen corporate criminal liability and integrate agrarian and environmental policies to ensure ecological protection and uphold the rights of indigenous communities.